Differences in knowledge of dementia among older adults with normal cognition, mild cognitive impairment, and dementia: A representative nationwide sample of Korean elders. (September 2016) - Lee, Jun-Young; Park, Soowon; Kim, Ki Woong; Kwon, Ji Eyon; Park, Joon Hyuk; Kim, Moon Doo; Kim, Bong-Jo; Kim, Jeong Lan; Moon, Seok Woo; Bae, Jae Nam; Ryu, Seung-Ho; Yoon, Jong Chul; et al.
Highlights: Korean elders had a low accuracy rate of 62%. Knowledge of dementia (KOD) decreased with cognitive impairment. KOD scores in the normal-cognition group were higher among highly educated, younger, literate women with no depression and a family history of dementia. Literacy emerged as the only contributor to knowledge of dementia among those with Alzheimer's disease. Abstract: Objective: Lack of knowledge about a disease could impede early diagnosis and may lead to delays in seeking appropriate medical care. The aim of this study was to explore knowledge of dementia (KOD) and to find the determinants of KOD among three groups: older adults with normal cognition, mild cognitive impairment (MCI), and dementia. Methods: A representative nationwide sample of 6141 Korean elders aged 65 years or older participated in face-to-face interviews and answered 14 questions pertaining to general information, etiology, symptoms, and treatment of dementia. Stepwise multiple regressions and path analyses probed the relationships between various sociodemographic variables and KOD. Results: The percentage of correct responses was only 62%. The item 'A person who remembers things that happened in the past does not have dementia' was answered correctly (false) by only 24.8–27% of the respondents in all groups. Older adults with normal cognition had higher KOD scores than those with MCI or dementia. In the normal-cognition group, KOD scores were higher among highly educated, younger, and literate women with no depression and a family history of dementia. In contrast with the determinants in the normal-cognition group, only the ability to read and write predicted KOD scores in the dementia group. Conclusions: Efforts to enhance KOD in elder adults are needed. Public education regarding the differences between dementia and healthy aging may increase KOD among normal elders and those with MCI. Among elders with dementia, educational materials that do not require literacy may be more helpful in increasing KOD with the aim of preventing treatment delay.